2015 CRISIS AND COLLECTIVE BARGAINING IN ARGENTINA: NEGATIVE NEGOTIATION AS A GOVERNMENT STRATEGY - da Costa, Flávio Ribeiro (Seven Editora, 2026)
This study analyzes the impacts of the 2015 economic crisis in Argentina on collective bargaining, with an emphasis on the strategy of "negative collective bargaining," defined as the deliberate limitation of wage demands and the capacity for union pressure due to restrictive macroeconomic targets. It hypothesizes that, in a context of high inflation and economic slowdown, the State intervened restrictively in negotiations, imposing limits on wage increases, especially in strategic sectors (Actis & Creus, 2015; Etchemendy & Collier, 2007). The research is qualitative, based on a literature review and document analysis, including classic and contemporary studies on labor relations and union data (Gramsci, 1991; Hyman, 1981; Kelly, 1998; Marticorena, 2014). The results indicate that collective bargaining was not eliminated, but reconfigured as a space for dispute, in which the government disciplined union action and controlled the dynamics of labor conflicts. Despite the restrictions, unionism maintained its leading role, especially at the grassroots level, demonstrating the persistence of collective mobilization as a mechanism of resistance.